The Effect of Transactional Leadership on Work Performance with Organizational Commitment as A Mediating Variable In BPJS Ketenagakerjaan Branch Office Se-Medan Raya - Desi Syahrani; Mesra B (Neo Journal of economy and social humanities, 2024)
In this study, researchers wanted to see the direct and indirect effects between transactional leadership variables as independent variables and organizational commitment as a mediating variable and work performance as the dependent variable. This type of research uses quantitative, this research was conducted at BPJS Employment Branches throughout Greater Medan consisting of BPJS Employment City Medan Branch Office, North Medan Branch, Tanjung Morawa Branch and Binjai Branch. The population of this study was 82 employees and the sample used was all the population using the saturated sample technique. The data source used is primary data sources and data collection is done by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measurement tool. The results of this study are as follows transactional leadership has a positive and significant effect on organizational commitment with an original sample value of 0.683 and P values of 0.000. Transactional leadership has a positive and significant effect on work performance with an original sample value of 0.391 and p values of 0.012. Organizational commitment has a positive and significant effect on job performance with an original sample value of 0.177 and p values of 0.001. Transactional leadership has a positive and significant effect on work performance through organizational commitment directly with the original sample result of 0.124 and p values 0.003.